-7(-1+5v)-5v=-39+6v

Simple and best practice solution for -7(-1+5v)-5v=-39+6v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(-1+5v)-5v=-39+6v equation:


Simplifying
-7(-1 + 5v) + -5v = -39 + 6v
(-1 * -7 + 5v * -7) + -5v = -39 + 6v
(7 + -35v) + -5v = -39 + 6v

Combine like terms: -35v + -5v = -40v
7 + -40v = -39 + 6v

Solving
7 + -40v = -39 + 6v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-6v' to each side of the equation.
7 + -40v + -6v = -39 + 6v + -6v

Combine like terms: -40v + -6v = -46v
7 + -46v = -39 + 6v + -6v

Combine like terms: 6v + -6v = 0
7 + -46v = -39 + 0
7 + -46v = -39

Add '-7' to each side of the equation.
7 + -7 + -46v = -39 + -7

Combine like terms: 7 + -7 = 0
0 + -46v = -39 + -7
-46v = -39 + -7

Combine like terms: -39 + -7 = -46
-46v = -46

Divide each side by '-46'.
v = 1

Simplifying
v = 1

See similar equations:

| 4(2y-5)+5y=7 | | 5x+4=8x-12 | | 6x-12-2x=5x-2 | | -4=-4r+32 | | 4-5v=-46 | | -1.5=x-0.1/0.2 | | 7(v+75)=938 | | -2+6(5b-4)=7(b+4)+5b | | -22=-13r+4 | | 5r^3(2r^1/2) | | 8+10m-1=7m+21-4m | | y=y-y | | y+5=10(x+9) | | 4x+8=-7x+10 | | 5r^3✖️2r^1/2 | | 3t-6=-9 | | -.83y+0.17=.72y | | 4p-12=20p-24 | | 30n-38=5(1+6n) | | 2d+4=10+2.4d | | y+2=.25(x+4) | | 5(x)=20(1.93)x | | -7b-5=-7b-8 | | 2+3-90=r | | 1/3x-2=x-4 | | 5(x)=20(1.93)xX | | 17x=1500+-12y | | -19=5r-4 | | 14y+8=-34 | | y-10=.25(x-4) | | 6/11(x-5)=6 | | (2x-15)+(x+35)=180 |

Equations solver categories